Inpatient neurosurgical mortality in Germany: a comprehensive analysis of 2023 in-hospital data - Kamp, Marcel; Jungk, Christine; Schneider, Matthias; Fehler, Georgia; Santacroce, Antonio; Dinc, N.; Ebner, Florian H.; von Sass, Christiane (Neurosurgical review, 2025)
Neurosurgical conditions and procedures are associated with varying in-hospital mortality rates, which represent one of several quality indicators. This study aims to determine and report in-hospital mortality rates across German neurosurgical departments in 2023. - Methods: A cross-sectional analysis of all neurosurgical cases treated in Germany in 2023 was conducted using nationwide hospital billing data reported under § 21 of the Hospital Remuneration Act. In-hospital mortality was defined as death during hospitalization (discharge status: deceased). - Results: Neurosurgical departments treated 222,158 inpatient cases, with 49% female and 48% aged ≥ 65 years. The overall mortality rate was 3.8% (8,338 cases), with significantly lower rates in females (3.3% vs. 4.2%, p < 0.0001). The most common fatal diagnoses included traumatic subdural hematomas (1,278 cases), subcortical intracerebral hemorrhages (611 cases) and traumatic subarachnoid hemorrhages (504 cases). Mortality rates varied by diagnosis: malignant brain tumors (4%), cerebral metastases (6%), benign meningeal tumors (1.3%), non-traumatic subarachnoid hemorrhages (7%), intracerebral hemorrhages (29%), and traumatic subdural hematomas (12%). Mortality for selected procedures was 3% for primary brain tumor resections, 9% for vascular reconstructions, 1% for spinal fusions, 2% for dynamic stabilizations, and 4% for vertebral body replacements. - Conclusions: This study analyzes and reports neurosurgical in-hospital mortality rates in Germany, providing a national benchmark that may inform clinicians, policymakers, and patients. While the use of administrative billing data imposes inherent limitations - particularly regarding clinical detail and causality - the findings may offer a foundation for future research. Subsequent studies should aim to explore disease- and procedure-specific mortality more granularly and may identify underlying risk factors.